Delayed creative destruction: How uncertainty shapes corporate assets - Campello, Murillo; Kankanhalli, Gaurav; Kim, Hyunseob (Journal of Financial Economics, 2024)
We show how uncertainty shapes corporate asset allocation, composition, and productivity using data from the shipping industry. Firms curtail both ship acquisitions and disposals when uncertainty increases, primarily through cuts in new ship orders and ship demolitions — decisions that are costlier to reverse vis-à-vis secondary market transactions. Uncertainty also prompts firms to concentrate their fleets into narrower, less productive portfolios. We corroborate our findings using the 2009–2011 spike in Somali pirate attacks as an uncertainty shock to shipping activity. Uncertainty hampers “creative destruction,” slowing both the adoption of innovation embodied in new capital and the disposal of old capital.